The ambiguous role of ethnic context: A multi-level analysis of the relationship between group size and labor market integration of three immigrant groups in Germany - Friedrich Scheller (Universität Duisburg-Essen, Institut für Soziologie, 2017)
The paper analyses the role of the relative regional group size for the labor market integration of three different ethnic groups in Germany. The analysis addresses the question of whether there is a consistent group size effect, or if group size functions differently for different immigrant groups and for different indicators of labor market integration in Germany. Using data provided by the German Socio-Economic Panel Study (SOEP) multilevel cross-classification models are fitted. The final dataset contains 10,970 observations from Turkish, Greek, and Italian immigrants, and their offspring. Results generally show no effect of relative regional group size on the risk of unemployment, but a significant effect on job status. The effect is nonlinear, and manifests differently for each ethnic group. It becomes apparent that findings on the relationship between group size and labor market integration found for one immigrant group cannot readily be extended to other origin groups. – – Der Aufsatz analysiert die Bedeutung des regionalen Bevölkerungsanteils einer Herkunftsgruppe für die Arbeitsmarktintegration von drei Migrantengruppen in Deutschland. Dabei wird untersucht, ob ein einheitlicher Effekt der Gruppengröße besteht, oder ob sich die Gruppengröße für verschiedene Migrantengruppen und verschiedene Indikatoren der Arbeitsmarktintegration unterschiedlich auswirkt. Für die Analyse werden Daten des Sozio-oekonomischen Panels (SOEP) verwendet und kreuzklassifizierte Mehrebenenmodelle geschätzt. Der verwendete Datensatz enthält 10.970 Beobachtungen von Befragten mit türkischem, griechischem oder italienischem Migrationshintergrund. Es zeigt sich grundsätzlich kein signifikanter Effekt der regionalen Gruppengröße auf das Arbeitslosigkeitsrisiko. Für den Status Erwerbstätiger findet sich ein signifikanter, nichtlinearer Effekt, der allerdings zwischen den verschiedenen Herkunftsgruppen variiert. Deutlich wird, dass Ergebnisse zum Zusammenhang zwischen regionaler Gruppengröße und der Arbeitsmarktintegration einer Herkunftsgruppe nicht auf andere Herkunftsgruppen (und Indikatoren der Arbeitsmarktintegration) übertragen werden können.
urn:nbn:de:hbz:464-20170720-114744-9
Keywords: 300; group size; labor market integration; migration; cross-classification; Gruppengröße; Arbeitsmarktintegration; Migration; Kreuzklassifizierung